312. Clinical Attributes and Risk Factors for In- Hospital Mortality among Covid-19 Patients in a Community Hospital Setting: A Propensity Matched Analysis. (4th December 2021) - Seetharam, Karthik; Bhat, Premila; Kumar, Kelash; Wai, Thinzar; Yenugadhati, Vamsi; Desai, Bhargav; Tamsukhin, Christina; Jafar, Shurovi; Castellon, Diego; Badem, Olga; Mir, Tanveer; Vargas, Sadisept; et al.
Abstract: Background: New York City emerged as the Epicenter for Covid-19 due to novel Coronavirus SARS-CoV-2 soon after it was declared a Global Pandemic in early 2020 by the WHO. Covid-19 presents with a wide spectrum of illness from asymptomatic to severe respiratory failure, shock, multiorgan failure and death. Although the overall fatality rate is low, there is significant mortality among hospitalized patients. There is limited information exploring the impact of Covid-19 in community hospital settings in ethnically diverse populations. We aimed to identify risk factors for Covid-19 mortality in our institution. Methods: We conducted a retrospective cohort study of hospitalized in our institution for Covid 19 from March 1 st to June 21 st 2020. It comprised of 425 discharged patients and 245 expired patients. Information was extracted from our EMR which included demographics, presenting symptoms, and laboratory data. We propensity matched 245 expired patients with a concurrent cohort of discharged patients. Statistically significant covariates were applied in matching, which included age, gender, race, body mass index (BMI), diabetes mellitus, and hypertension. The admission clinical attributes and laboratory parameters and outcomes were analyzed. Results: The mean age of the matched cohort was 66.9 years. Expired patients had a higher incidence of dyspnea (P < 0.001) and headache (0.031). In addition, expired patients had elevated CRP- hs (mg/dl) ≥ 123 (< .0001), SGOT or AST (IU/L) ≥ 54 (p < 0.001), SGPT or ALT (IU/L) ≥ 41 (p < 0.001), and creatinine (mg/dl) ≥ 1.135 (0.001), lower WBC counts (k/ul) ≥ 8.42 (0.009). Furthermore, on multivariate logistic regression, dyspnea (OR = 2.56, P < 0.001), creatinine ≥ 1.135 (OR = 1.79, P = 0.007), LDH(U/L) > 465 (OR = 2.18, P = 0.001), systolic blood pressure < 90 mm Hg (OR = 4.28, p = .02), respiratory rate > 24 (OR = 2.88, p = .001), absolute lymphocyte percent (≤ 12%) (OR = 1.68, p = .001) and procalcitonin (ng/ml) ≥ 0.305 (OR = 1.71, P = .027) predicted in- hospital mortality in all matched patients. Conclusion: Our case series provides admission clinical characteristics and laboratory parameters that predict in- hospital mortality in propensity Covid 19 matched patients with a large Hispanic population. These risk factors will require further validation. Disclosures: All Authors : No reported disclosures